Estimation of glucose rate of appearance in portal vein circulation using a phenomenological-based model (2023)
The joint work of the stomach and the small intestine plays a fundamental role in human digestion. In the stomach, food is turned into a semi-fluid mixture that is slowly released into the small intestine, where most enzymatic reactions occur, and nutrients are absorbed as they become available. This whole process is closely related to glucose homeostasis, mainly because of the appearance of glucose in the portal system and the energetic expenditure of the process itself. The current phenomenological-based model describes such effects of the digestive process on blood glucose concentration. It considers enzymatic and mechanical transformations, energetic expenditure, and the impact of macro-nutrients, fiber, and water on overall digestion and glucose absorption. The model estimates the rate of glucose appearance in the portal vein and is intended to be further integrated into existing models for other human organs and used in model-based systems such as an artificial pancreas with automated insulin delivery.